2013
DOI: 10.1016/j.bbrc.2013.10.159
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Parkinson’s disease mutations across the functional domains of LRRK2 alter the autophagic/lysosomal response to starvation

Abstract: HighlightsMutations in the ROC, COR and Kinase domain of LRRK2 alter the autophagic response to starvation.LC3-I/II ratio following starvation is altered by mutations, as well as p62 and WIPI2 positive puncta.This occurs independently of any alteration in downstream targets of mTORC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 33 publications
2
67
0
Order By: Relevance
“…Via interactions with multiple molecules, leucine-rich repeat kinase 2 (LRRK2) functions in apoptosis (10), protein synthesis (11,12), and cytoskeletal dynamics (13)(14)(15). Recently, several reports have demonstrated that LRRK2 controls autophagy (16)(17)(18)(19)(20). Owing to this diversity of function, despite intense interest and extensive study, the mechanisms by which LRRK2 mutations cause neurodegeneration remain unclear.…”
mentioning
confidence: 99%
“…Via interactions with multiple molecules, leucine-rich repeat kinase 2 (LRRK2) functions in apoptosis (10), protein synthesis (11,12), and cytoskeletal dynamics (13)(14)(15). Recently, several reports have demonstrated that LRRK2 controls autophagy (16)(17)(18)(19)(20). Owing to this diversity of function, despite intense interest and extensive study, the mechanisms by which LRRK2 mutations cause neurodegeneration remain unclear.…”
mentioning
confidence: 99%
“…Even though the brain of LRRK2 knockout mice did not recapitulate the pathological hallmarks of PD, a biphasic alteration in macroautophagy has been observed in the kidneys, with enhanced autophagy at young ages and reduced autophagy at old ages 112. The use of human fibroblasts carrying LRRK2 pathogenic mutations has confirmed an alteration in autophagy with reports suggesting an increase in basal macroautophagy in G2019S carriers 113, or an impaired response to starvation‐induced macroautophagy across mutations in the LRRK2 catalytic core ( G2019S , Y1699C and R1441G ) 114. The use of induced Pluripotent Stem cell (iPSC)‐derived, human dopaminergic neurons carrying G2019S ‐LRRK2 has confirmed a reduction in macroautophagy in comparison with healthy controls 115; but again, details of the molecular mechanism underlying this are still ambiguous.…”
Section: Lrrk2 and Autophagymentioning
confidence: 96%
“…This effect is presumably related to the known function of LRRK2 in autophagy (18,24,33,37,38) but can be tied mechanistically to disruption of TGN. Interestingly, autophagic vesicles may derive from the trans-Golgi network (37); hence, altered turnover of Golgi-derived vesicles would impact autophagy function over time, consistent with effects of LRRK2 deficiency in animal models (34).…”
Section: Discussionmentioning
confidence: 99%